Xylanases from fungi: properties and industrial applications - Polizeli, MLTM; Rizzatti, ACS; Monti, Rubens [UNESP]; Terenzi, H. F.; Jorge, J. A.; Amorim, D. S. (Springer, 2005)
Xylan is the principal type of hemicellulose. It is a linear polymer of beta-D-xylopyranosyl units linked by (1-4) glycosidic bonds. In nature, the polysaccharide backbone may be added to 4-O-methyl-alpha-D-glucuronopyranosyl units, acetyl groups, alpha-L-arabinofuranosyl, etc., in variable proportions. An enzymatic complex is responsible for the hydrolysis of xylan, but the main enzymes involved are endo-1,4-beta-xylanase and beta-xylosidase. These enzymes are produced by fungi, bacteria, yeast, marine algae, protozoans, snails, crustaceans, insect, seeds, etc., but the principal commercial source is filamentous fungi. Recently, there has been much industrial interest in xylan and its hydrolytic enzymatic complex, as a supplement in animal feed, for the manufacture of bread, food and drinks, textiles, bleaching of cellulose pulp, ethanol and xylitol production. This review describes some properties of xylan and its metabolism, as well as the biochemical properties of xylanases and their commercial applications.